The Natural Radioactivity and Accompanying Radiation Hazard in the Tigris River Sediments in Baghdad, Iraq - Hussian, Hussian A.; Ali, Kamal K. (Iraqi Journal of Science, 2024)
The natural radioactivity in the sediments of the Tigris River was measured using gamma spectrometry using an HPGe detector. Ten sediment samples were collected, and the target radionuclides are 226Ra, 232Th and 40K. Radioactivity in sediment was investigated in clay and silt fractions beside the hazard indices. The 226Ra concentration ranged between 6.5 and 11.2 Bq/kg, 232Th from 4.1 to 9.6 Bq/kg, and 40K from 133.8 to 260.2 Bq/kg. The average values of the natural radionuclides of these elements are within the worldwide average or less and comparable to those of the rivers in other countries; accordingly, the radiological hazard indices such as absorbed dose rate, annual effective dose equivalent, hazard indices and gamma index are below the recommended international values, indicating no significant hazard. The study concluded a positive relationship between the radioactivity and clay and silt content.